2018
DOI: 10.1038/s41388-018-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of STAT3 and Bcl-2 and reduction of reactive oxygen species (ROS) promote radioresistance in breast cancer and overcome of radioresistance with niclosamide

Abstract: Radiotherapy significantly improves the therapeutic outcomes and survival of breast cancer patients. However, the acquired resistance to this therapeutic modality is a major clinical challenge. Here we show that ionizing irradiation (IR)-induced phosphorylation of signal transducer and activator of transcription 3 (STAT3) at the Tyr705 residue and the induction of reactive oxygen species (ROS) in wild-type and radioresistant MDA-MB-231 and MDA-MB-468 triple-negative breast cancer (TNBC) cell lines. Comparing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 54 publications
8
101
0
Order By: Relevance
“…Consistent with our results, other studies reported that MDA‐MB‐231 cells demonstrated a higher survival fraction than MDA‐MB‐468 cells after 2 or 4 Gy 28,29 . However, the differences in colony formation between MDA‐MB‐468 and MDA‐MB‐231 cells after 4 Gy were not significant 30 . It was recently reported that PI3K/AKT inhibitor inhibited the resistance to endocrine or DNA‐damaging radiotherapy in ER‐positive early patients with BC 31 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, other studies reported that MDA‐MB‐231 cells demonstrated a higher survival fraction than MDA‐MB‐468 cells after 2 or 4 Gy 28,29 . However, the differences in colony formation between MDA‐MB‐468 and MDA‐MB‐231 cells after 4 Gy were not significant 30 . It was recently reported that PI3K/AKT inhibitor inhibited the resistance to endocrine or DNA‐damaging radiotherapy in ER‐positive early patients with BC 31 .…”
Section: Discussionsupporting
confidence: 91%
“…HJC0152 also decreases the antioxidant capacity of A549 cells and increases ROS levels. When ROS is accumulated to a level higher than the antioxidant capacity of cells, oxidative stress occurs, leading to apoptosis . Our results also showed that HJC0152 induces apoptosis in A549 NSCLC cells.…”
Section: Discussionsupporting
confidence: 69%
“…Previously, we found that oxidative stress is an early upstream event of apoptosis in breast cancer cells . To assess whether HJC0152 induces apoptosis in lung cancer cells, we performed annexin V‐FITC/PI double staining and analysis using flow cytometry .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations